2022
DOI: 10.3390/ijerph19127253
|View full text |Cite
|
Sign up to set email alerts
|

Prior to Implementation of Digital Pathology—Assessment of Expectations among Staff by Means of Normalization Process Theory

Abstract: The Region of Southern Denmark is the first in Denmark to implement digital pathology (DIPA), starting at the end of 2020. The DIPA process involves changes in workflow, and the pathologist will have to diagnose based on digital whole slide imaging instead of through the traditional use of the conventional light microscope and glass slides. In addition, in the laboratory, the employees will have to implement one more step to their workflow—scanning of tissue. The aim of our study was to assess the expectations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 17 publications
1
1
1
1
Order By: Relevance
“…Our results are aligned with the conclusions reached by previous studies that used NPT to assess expectations prior to the implementation of DIPA and found that the participants “reported feeling sufficiently tech-savvy to be able to use DIPA” and had high expectations, motivation, and readiness for the upcoming changes [ 12 ]. However, the employees were skeptical regarding the allocation of resources, and few were aware of reports about the effects of DIPA.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our results are aligned with the conclusions reached by previous studies that used NPT to assess expectations prior to the implementation of DIPA and found that the participants “reported feeling sufficiently tech-savvy to be able to use DIPA” and had high expectations, motivation, and readiness for the upcoming changes [ 12 ]. However, the employees were skeptical regarding the allocation of resources, and few were aware of reports about the effects of DIPA.…”
Section: Discussionsupporting
confidence: 90%
“…Previous research about the expectations of health care staff prior to the implementation of digital pathology (DIPA) by means of NPT in the form of semistructured interviews and the Normalization Measure Development (NoMAD) questionnaire was carried out [ 12 , 13 ]. Overall, the authors reported staff feeling sufficiently tech-savvy to be able to use DIPA, having high expectations as well as motivation and readiness for the upcoming changes.…”
Section: Introductionmentioning
confidence: 99%
“…The overall NoMAD score in our study also indicated a high normalization of the use of guided iCBT for mild to moderate anxiety and depressive disorders at both baseline and 6-month follow-up. Compared with other studies that had used the NoMAD questionnaire to assess the degree of normalization, the respondents in our study indicated a high degree of normalization using guided iCBT ( 44 48 ). This can be explained by the respondents' high sense of being part of the implementation, which was also reflected in the interviews.…”
Section: Discussioncontrasting
confidence: 82%
“…Die Arbeitsgruppe um Mikkelsen et al. erwartet beispielsweise eine jährliche Zunahme pathologischer Fälle in Süddänemark von 4,5 % [ 3 ]. Der Fachkräftemangel in der Pathologie wird von vielen Autor:innen als globales Problem angesehen, von dem auch Deutschland betroffen ist [ 5 ].…”
unclassified